Social Aspects of Religious Matters in the Comparative Analysis of the Historical and Contemporary Feature Materials of Kazakhstan. / Aspectos sociales de las cuestiones religiosas en el análisis comparativo de los materiales históricos y contemporáneos de Kazajstán - Sailaukyzy, Alma; Yertassova, Gulzhazira; Sak, Kairat; Kurman, Nessibeli (Utopía y Praxis Latinoamericana)
ABSTRACT The paper deals with the relevant problems of religion in the Kazakhstan society and social components of the national unity in the historical prerequisites. The authors have studied the Alash intelligentsia, particularly, their influence on the formation of the public opinion regarding the acute religious problems. The authors have also considered the problem of the religious fanaticism in the context of the state’s choice of the way for the secular way of development. They have concluded that the government having based on the secular and democratic principles, adopted various measures to solve the religious disagreements in the country. RESUMEN El documento aborda los problemas relevantes de la religión en la sociedad de Kazajstán y los componentes sociales de la unidad nacional en los requisitos históricos. Los autores han estudiado la intelectualidad Alash, en particular, su influencia en la formación de la opinión pública sobre los problemas religiosos agudos. Los autores también han considerado el problema del fanatismo religioso en el contexto de la elección del estado como el camino para el desarrollo secular. Han llegado a la conclusión de que el gobierno, basándose en los principios seculares y democráticos, adoptó diversas medidas para resolver los desacuerdos religiosos en el país.